Patterns of discipleship in the New Testament - Longenecker, Richard Norman, 1930- (Grand Rapids, MI Eerdmans, 1996)
Includes bibliographical references and indexes.
Keywords: Christian life -- discipleship -- Pauline theology; Bible. N.T. -- criticism, interpretation, etc; Christian life -- Biblical teaching